HUBUNGAN KONTROL DIRI DENGAN FEAR OF MISSING OUT (FOMO)PADA REMAJA PENGGUNA MEDIA SOSIAL - Safira Maza; Rizqi Amalia Aprianty (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
Fear of missing out (FOMO) is a phenomenon in which individuals feelafraid of being left behind, anxious and nervous if you haven't checked social media accounts, obsessed with other people's activities, causing an uncontrollable desire to stay connected to the activities of other people on social media. The purpose of this study was to determine the relationship between self-control and fear of missing out (FOMO) in adolescent social media users. This research method uses a quantitative approach to the type of correlational research. Sampling in this study used a non-prabability sampling technique with purposive sampling method. The subjects of this study were adolescent social media users with an age range of 18-21 years in the city of Banjarmasin as many as 347 subjects. The scale used in this study is the self-control scale and the fear of missing out (FOMO) scale, with a scaling model that is a Likert scale. The analysis used is Pearson's product moment correlation. The results showed that there was a negative and significant relationship between self-control and fear of missing out (FOMO) with a coefficient (r) of -729 with a value (Sig.) of 0.000. Through the results of data processing with statistical tests, it can be said that the researcher's hypothesis in this study is acceptable because the results obtained indicate a significant negative relationship between self-control and fear of missing out (FOMO) in adolescent social media users.